The equation above is not reducible to the Clairaut's Form as it can't be put in the form
"y = xp +f(p)"
To solve this equation, simple use "x^2p^2-2xyp+y^2-x^2 = 0"
Factorizing the above equation.
we get, "y = xp - x" and "y = xp +x"
Solving the equations,
"y = x(\\frac{dy}{dx} - 1) \\implies \\frac{dy}{dx} - \\frac{y}{x} = 1"
I.F. "e^{- \\int \\frac{dx}{x} } = \\frac{1}{x}"
Then,
"\\frac{1}{x} y = \\int \\frac{1}{x} dx"
"\\frac{1}{x} y = lnx + ln C"
"y = x(lnx + ln C) = xln(Cx)"
Similarly for "y = x(p+1) \\implies \\frac{dy}{dx} - \\frac{y}{x} = -1"
I.F. "e^{- \\int \\frac{dx}{x} } = \\frac{1}{x}"
"\\frac{1}{x} y = \\int -\\frac{1}{x} dx"
"y = -x(lnx + ln C) = -xln(Cx)"
Comments
Leave a comment